Dissecting the mechanisms of pathogenesis in cerebral malaria. - Arathy Ramachandran; Amit Sharma (PLoS Pathogens, 2022)
Cerebral malaria (CM) is one of the leading causes of death due to malaria. It is characterised by coma, presence of asexual parasites in blood smear, and absence of any other reason that can cause encephalopathy. The fatality rate for CM is high, and those who survive CM often experience long-term sequelae, including cognitive and motor dysfunctions. It is unclear how parasites sequestered in the lumen of endothelial cells of the blood-brain barrier (BBB), and localised breakdown of BBB can manifest gross physiological changes across the brain. The pathological changes associated with CM are mainly due to the dysregulation of inflammatory and coagulation pathways. Other factors like host and parasite genetics, transmission intensity, and the host's immune status are likely to play a role in the development and progression of CM. This work focuses on the pathological mechanisms underlying CM. Insights from humans, mice, and in vitro studies have been summarised to present a cohesive understanding of molecular mechanisms involved in CM pathology.